Targeting the Immune System With Mesenchymal Stromal Cell-Derived Extracellular Vesicles: What Is the Cargo's Mechanism of Action? - Martin-Rufino, Jorge Diego; Espinosa-Lara, Natalia; Osugui, Lika; Sanchez-Guijo, Fermin (Frontiers in Bioengineering and Biotechnology, 2019)
The potent immunomodulatory activities displayed by mesenchymal stromal cells (MSCs) have motivated their application in hundreds of clinical trials to date. In some countries, they have subsequently been approved for the treatment of immune disorders such as Crohn’s disease and graft-versus-host disease. Increasing evidence suggests that their main mechanism of action in vivo relies on paracrine signaling and extracellular vesicles. Mesenchymal stromal cell-derived extracellular vesicles (MSC-EVs) play a prominent role in intercellular communication by allowing the horizontal transfer of microRNAs, mRNAs, proteins, lipids and other bioactive molecules between MSCs and their targets. However, despite the considerable momentum gained by MSC-EV research, the precise mechanism by which MSC-EVs interact with the immune system is still debated. Available evidence is highly context-dependent and fragmentary, with a limited number of reports trying to link their efficacy to specific active components shuttled within them. In this concise review, currently available evidence on the molecular mechanisms underlying the effects of MSC-EV cargo on the immune system is analyzed. Studies that pinpoint specific MSC-EV-borne mediators of immunomodulation are highlighted, with a focus on the signaling events triggered by MSC-EVs in target immune cells. Reports that study the effects of preconditioning or “licensing” in MSC-EV-mediated immunomodulation are also presented. The need for further studies that dissect the mechanisms of MSC-EV cargo in the adaptive immune system is emphasized. Finally, the major challenges that need to be addressed to harness the full potential of these signaling vehicles are discussed, with the ultimate goal of effectively translating MSC-EV treatments into the clinic.